Management modes and effects analysis of strengthening the volunteer’s normalized nucleic acid sampling (加强志愿者常态化核酸采样的管理方法与效果) - HAN Chunying (韩春英); YOU Chenggang (尤诚刚); PAN Meili (潘美丽); JIANG Yuting (蒋玉婷); XU Yiwen (徐伊雯); LU Weijie (陆玮婕); XIA Hui (夏卉); CHEN Haiyan (陈海燕); HUANG Ying (黄莹); GU Yuanlu (顾元露); CHEN Huiying (陈慧颖); ZHANG Qi (张琪); et al. (中西医结合护理)
Objective To discuss the management modes and application effects of strengthening the volunteer’s normalized nucleic acid sampling. Methods The volunteers of receiving the nucleic acid sampling training and normalized nucleic acid sampling (May 1st, 2022 to Jun 30th, 2022) were investigated. The volunteers were assigned to control group (n=300) and test group (n=300). WeChat group and self-made questionnaires were developed while the normalized nucleic acid sampling manuals were delivered. The normalized nucleic acid sampling was applied in the control group, and the theoretical knowledge and professional skills training were applied in the test group weekly. The weekly examination performances were evaluated through the questionnaires and interviews. The job-site sampling quality was assessed. Results Both of groups had participated into the nucleic acid sampling training and had working experiences. Before intervention, the standard rates of the job-site supervision and theoretical knowledge were 100% in both two groups. There was no significant difference in the theoretical knowledge and job-site supervision scores between groups (P>0. 05). After intervention, the theoretical knowledge and job-site supervision scores for two groups showed a rising tendency; After 1w, 2w, 3w and 4w of intervention, the cognitive levels and theoretical knowledge scores in the test group were significantly higher than those in the control group (P＜0. 05); After intervention, the occupational exposure rates in the test group were significantly lower than that in the control group (P＜0. 05). Conclusion Volunteer’s normalized nucleic acid sampling management should be enhanced from aspects of job-site supervision, the professional skill and theoretical knowledge learning, the volunteer’s job responsibility and specific rule planning, so as to increase the nucleic acid sampling normalization and accuracy. (目的 探讨加强志愿者常态化核酸采样的管理方法, 并观察其应用效果。方法 选取2022年5月1日—6月30日在本院接受核酸采样培训的并参加常态化核酸采样的志愿者进行研究, 根据电脑随机分组将志愿者分为对照组和研究组, 各300人。建立微信群, 通过“问卷星”进行在线问卷调查, 每人发放常态化核酸采样手册。对照组进行常态化核酸采样, 研究组每周完成相关理论及技能的再培训。每周通过问卷和走访的形式对两组志愿者进行考核, 并对志愿者工作现场进行质量检查。结果 两组均为参加过培训及有一定工作经验的志愿者, 干预前对两组进行现场督查和理论考核, 考核达标率均为100%, 两组理论考核及现场结果差异无统计学意义(P＞0. 05)。干预后, 两组理论考核及现场结果督查成绩均呈上升趋势, 但研究组志愿者干预后1、2、3、4周对核酸采样各方面的认知水平和理论考核的上升幅度明显优于对照组(P＜0. 05); 研究组加强志愿者管理后职业暴露发生率低于对照组(P＜0. 05)。结论 加强志愿者常态化核酸采样管理需从加强督察督办、强化志愿者各项培训和理论学习、明确志愿者的岗位职责和具体制度三方面展开, 能够确保志愿者采样的规范性和准确性。)